Reframing a problem: identifying the sources of conflict in a teacher education course. Issue 5 (20th October 2017) - Quebec Fuentes, Sarah; Bloom, Mark
Abstract: This article exemplifies the critical initial phase of action research, problem identification, in the context of a teacher education course. After frustration arose between preservice elementary teachers (PSTs) and their instructor over classwork quality, the instructor employed reflective journaling and discussions to examine the source of the conflict. Qualitative analysis of class reports, journal entries, and discussions revealed that PSTs' perceptions of their role in a teacher education course did not align with those of their instructor; goal orientation is used as a conceptual framework to contrast the perspectives. Implications of purposeful and methodical collection and analysis of data (in the initial stage of action research) include reframing a problem using data representing PSTs' perspectives; allowing instructors to carefully consider possible solution strategies; providing a democratic setting for learning by giving voice to PSTs; and modeling reflective practice as a mode of conflict resolution in an authentic classroom setting.